POLITENESS STRATEGY BY BALINESE AT PENGLIPURAN VILLAGE, BANGLI - Ni Wayan Prami Wahyudiantari (Journal of English Education and Literature, 2025)
This article provides a comprehensive examination of politeness strategies employed by the Balinese community in Penglipuran Village, Bangli, a culturally rich area renowned for its commitment to preserving traditional Balinese heritage and the Tri Hita Karana philosophy, which emphasizes harmony between humans, nature, and the spiritual realm. Utilizing a qualitative research design, the study involved detailed observations and interviews focusing on everyday social interactions between villagers and tourists, uncovering the nuanced ways politeness is linguistically and behaviorally enacted. The Balinese utilize positive politeness tactics such as warm greetings infused with traditional honorifics, inclusive language fostering a sense of shared identity, and proactive offers to guide or assist visitors, thereby creating a welcoming atmosphere that upholds community values. At the same time, negative politeness strategies are observed in the form of indirect speech acts or respectful distancing, especially within contexts that require setting boundaries or managing tourist numbers, which helps prevent discomfort or social conflict. These communicative practices are deeply interwoven with local customs, religious teachings, and community governance systems, facilitating not only smooth tourist-host interactions but also reinforcing social cohesion among residents amidst the pressures of modern tourism. The findings underscore how these politeness strategies are integral to sustaining a balanced, respectful environment that supports long-term, community-based tourism development in Penglipuran Village, ensuring both cultural preservation and economic vitality.